Parental kidnapping in America an historical and cultural analysis - Dabbagh, Maureen, 1958- (McFarland & Co., 2012)
"In 2010, the U.S. Department of Justice reported an average of 200,000 cases of parental kidnapping each year. This candid exploration from the eighteenth century to the present clarifies many misconceptions and reveals how the external influences of American social, political, legal, and religious culture can exacerbate family conflict, creating a social atmosphere ripe for abduction"--Provided by publisher.